Spatial-fluxomics provides a subcellular-compartmentalized view of reductive glutamine metabolism in cancer cells - Won Dong Lee (Nature Portfolio, 2019)
Measuring metabolic fluxes in cellular compartments is a challenge. Here, the authors introduce an approach to infer fluxes in mitochondria and cytosol, and find that IDH1 is the major producer of cytosolic citrate in HeLa cells and that in SDH- deficient cells citrate synthase functions in reverse.